Assessment of gingival sulcus depth, in primary, mixed and permanent dentition-Part-1 - Shivani, Singh; Vandana, K.L. (International Journal of Dental Research, 2017)
Aim and objective: The objective of this in-vivo study was to evaluate toothwise and archwise sulcus depth in human primary, mixed and permanent dentition of Indian population.Method: The study included 40 subjects (22 males and 18 females) of an age range 4-25 years. Subjects were divided into 3 groups â€“ the primary dentition (4-6 years) mixed dentition (7-13 years) and adult dentition (16-25 years). All the parameters were measured in upper and lower anterior segments.Results: Gingival sulcus depth (GSD) was measured archwise and toothwise in different dentitions and overall dentition wise without differentiating archwise and toothwise. GSD was significantly higher in maxillary mixed dentition (1.75Â±0.75) followed by permanent and primary dentition. In all the dentition, maxillary central incisor showed significant GSD.Conclusion: The sulcus depth is maximum in mixed dentition followed by primary and permanent dentitions and significantly higher in maxillary central incisor.